Analysis Of Noise Intensity In The Railway Facility Maintenance Work Environment - Ajeng Tyas Damayanti (Jurnal Syntax Transformation, 2023)
One example of work that has a high risk of work in the world of railways is the maintenance of railway facilities. One of the risks posed comes from the noise generated from the maintenance activities carried out. This study used a Soundlevel Meter tool to measure noise intensity in the railway facility maintenance work environment. The measured noise level is the equivalent noise level. This study also seeks to find out the impact and what impact prevention steps have been taken. The equivalent noise level in the work environment, especially in the final test, is 90.82 dB. The impact of noise experienced includes physiological disorders, psychological disorders and social disorders. Common physiological disorders experienced by facility nurses are the appearance of nausea, insomnia and shortness of breath. This feeling of discomfort will diminish and become less and less felt after some time. In the sense of hearing is also not found permanent interference. Psychological disorders can be in the form of discomfort, lack of concentration, insomnia, emotional instability, feelings of irritability to colleagues and superiors, and feeling tired quickly. One form of social disorder that can appear is masking effect, which is a lack of clear communication due to sounds that cover hearing. Noise control carried out is by isolating (separating facility nurses from noise sources), periodic toolbox meetings, administrative arrangements (setting working hours and facility nurses), providing K3 training, routine health checks, and using PPE properly and correctly.